Effect of microfinance services on the performance of micro-entrepreneurs: a study in pilimathalawa area. - Swarnika, K.; Pushpanathan, A. (Faculty of Business Studies, Vavuniya Campus of the University of Jaffna., 2020)
This study examines the effect of microfinance services on the performance of microentrepreneurs in the Pilimathalawa area. One hundred micro entrepreneurs received the benefits from the Samurdhi Bank selected as a sample in this study purpose. The microfinance services – micro-credit, micro-savings, and micro-training- are considered independent variables and entrepreneurs’ performance considered as dependent variables of the study. Data were collected through issuing a structured questionnaire to the respondents and analyzed using SPSS version 20. The Regression analysis and factor analysis were done for the effects of financial services on the performance of micro entrepreneurs. The present study results indicated that the microfinance services – micro-credit, micro-saving, and micro-finance have highly impact the performance of entrepreneurs. Finally, the microfinance services – credits, serving, and training - have highly effective on the performance of the microentrepreneurs. Further, the study recommended that the micro-savings has a higher effect on the entrepreneurs’ performance than that of other services.
Keywords: Micro-Entrepreneurs.; Microfinance Services; Performance